Research Progress on Pharmacological Effects and Mechanisms of Curcumin - Liu, Yuxing; Liu, Qingmei (Scientific Journal of Technology, 2025)
Curcumin belongs to a class of polyphenol compounds, and its source is the rhizome of turmeric (belonging to Zingiberaceae). This substance is the main component of turmeric releasing its own pharmacological activity. Pharmacological experiments have confirmed that It has anti-tumor, antioxidant and anti-inflammatory effects, accompanied by high efficiency and low toxicity. It also has high clinical promotion value. This paper reviews the pharmacological research progress of curcumin, hoping to provide new ideas for its clinical application and further research.